Osservazioni sulla decorazione della volta nella grotta degli Animali a Castello - Griffo, Alessandra (Opus Incertum, 2019)
This article focuses on details of the grotto’s vault which became evident during the restoration of the hydraulic system which originally sprayed on visitors from above and was operated as a court game. The are of the grotto is covered with calcareous sponges, shells, painted portions of plaster resembling mosaics, stucco in the shape of small fruits and small amounts of glass elements. In the central part of the main chamber there is no alignment of existing pipes; this is visible from the extrados and the holes still existing inside and is evidence that the layout of the vault was partly modified. Comparing it to other interventions by the House of Lorraine, it is suggested that this happened at the end of the eighteenth century. Following the taste of the time, the decoration was changed and rationalized; softer hues were introduced and a few remnants of shells painted in red and blue (visible at close inspection from the scaffoldings) recall what was probably the more colorful Medici grotto.